MNEMONICS IN TEACHING ARABIC GRAMMAR: A PILOT CASE STUDY ABOUT THE NUMERAL (Romano-arabica, 2025)
The retention of key grammatical concepts remains a challenge in contemporary grammar instruction. Memorization is a skill that can be developed to better address this issue. Mnemonics, a set of cognitive strategies to enhance memorization across domains including language, offer potential benefits. Considering the historic role of memorization in Arabic grammar pedagogy, the pilot experiment presented in this study examined the effect of mnemonics for teaching/learning the polar agreement of the Arabic numerals. Participants were divided into two groups: one received a concise mnemonic phrase framing the agreement rule and the other was given a conventional explicit grammar rule. The results revealed some suggestive trends of mnemonics facilitating learning while reducing cognitive overload. Although multiple experimental limitations preclude definitive conclusions, the findings provide a promising premise for a full-scale experiment that could yield more rigorous evidence and pedagogical insights.